The HFES Diversity Committee: Challenges and Opportunities for Involvement. (September 2017) - Chiou, Erin K.; Wooldridge, Abigail R.; Price, Morgan; Mosqueda, Euniqué; Roscoe, Rod
The Human Factors and Ergonomics Society Diversity Committee met initially in January 2017, and on a regular basis thereafter to assess and improve diversity and inclusion in the society, profession, and discipline. Charged by president Bill Marras in 2016, the Committee replaced the Diversity Task Force established in 1994, and formally became a part of the Society's Internal Affairs Division. As part of the Committee's initial outreach, this panel will continue the conversation with society members about diversity and inclusion. Panelists will provide an overview of the Committee's charter, review historical trends and current status of member diversity, discuss previous successful programming for enhancing diversity and feature perspectives from students and professionals in academia, industry, government/military/aerospace and consulting. Committee members welcome feedback and input from attendees on the above topics, what inclusion and diversity means and how to balance the broader concept of diversity with focused activities for targeted groups.